Increased glucose‐stimulated FGF21 response to oral glucose in obese nondiabetic subjects after Roux‐en‐Y gastric bypass. (17th October 2016) - Vienberg, S.G.; Jacobsen, S.H.; Worm, D.; Hvolris, L.E.; Naver, L.; Almdal, T.; Hansen, D.L.; Wulff, B.S.; Clausen, T.R.; Madsbad, S.; Holst, J.J.; Andersen, B.
Summary: Objective: The positive metabolic outcome of Roux‐en‐Y gastric bypass (RYGB) surgery may involve fibroblast growth factor 21 (FGF21), in both the fasting state and postprandially. We measured the fasting levels of FGF21 before and after bariatric surgery as well as the postprandial FGF21 responses after a glucose load and after a mixed meal. Design: Observational intervention trial. Patients and measurements: Eight obese, nondiabetic patients underwent RYGB. Plasma FGF21 was measured both before and after surgery on three different days during oral glucose loads (25 g or 50 g glucose) or a mixed meal. Blood samples were taken right before the meal and at 15‐min intervals until 90 min and at 150 min and 210 min relative to the start of the meal. Results: Overall, fasting plasma FGF21 did not change significantly before and after surgery (262 ± 71 vs 411 ± 119 pg/ml), but for three subjects, fasting plasma FGF21 increased significantly after surgery. Furthermore, FGF21 levels increased significantly at t = 90 and t = 150 min in response to 50 g glucose, but not after a mixed meal. Conclusions: In conclusion, the observed increase in postprandial plasma FGF21 in response to glucose and the lack of FGF21 response to a mixed meal may have important implications for the physiologic role of FGF21. The increase in postprandial FGF21 in response to glucose in the early postoperative period may contribute to the metabolic improvements observed after gastric bypass.